New German political document of 2021: the first German Strategy for sustainable financing - Ermakova, Elena P. (Journal of the Belarusian State University. Law, 2021)
The article notes that on 5 May 2021, the German federal government adopted a political document which is the first German Strategy for sustainable financing. The strategy consists of 26 individual measures. The core set of measures includes redirecting federal investment to sustainable investment, labeling sustainability to consumers («traffic light» tags). The nongovernmental organisation Germanwatch criticised the measures proposed in the strategy for being largely too vague.
Keywords: German law; green finance; energy transition; sustainable financing strategy